2023
DOI: 10.1108/ec-01-2023-0013
|View full text |Cite
|
Sign up to set email alerts
|

Stratal movement and microseismic events induced by multi-well hydrofracturing under varying well spacings and initiation sequences

Yongliang Wang,
Liangchun Li,
Yang Ju

Abstract: PurposeMulti-well hydrofracturing is a key technology in engineering, and the evaluation, control and optimization of the fracturing network determine the recovery rate of unconventional oil and gas production. In engineering terms, altering well spacing and perforation initiation sequences changes fracture propagation behavior. Fracture propagation can result in fracture-to-fracture and well-to-well interactions. This may be attributed to the interference between fractures caused by squeezing of the reservoir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In the study of microseismic events caused by multi-well hydraulic fracturing, it is found that stratal movement between multiple wells is positively correlated with microseismic events, and microseismic events can be effectively weakened by reducing stratal movement. Under different well spacing, the contact slip events caused by fracturing is obviously smaller than the damage events caused by hydraulic fracturing (Wang et al. , 2023a, b, c).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…In the study of microseismic events caused by multi-well hydraulic fracturing, it is found that stratal movement between multiple wells is positively correlated with microseismic events, and microseismic events can be effectively weakened by reducing stratal movement. Under different well spacing, the contact slip events caused by fracturing is obviously smaller than the damage events caused by hydraulic fracturing (Wang et al. , 2023a, b, c).…”
Section: Introductionmentioning
confidence: 96%
“…In addition, the well spacing also affects the formation deformation in fracture propagation. With the increase of well spacing, the effect of fracturing-induced stratal movement and squeezing deformation decrease (Wang et al. , 2023a, b, c).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spacing of perforation clusters, fracturing sequence and well spacing are the major factors causing the unstable propagation of parallel fractures to different degrees in the hydrofracturing process of multiple horizontal wells (Ghazal et al. , 2015; Kumar and Ghassemi, 2016; Wang et al. , 2023).…”
Section: Introductionmentioning
confidence: 99%